Conductometric and Spectrophotometric Studies on Copper(II), Zinc(II) and Cadmium(II) Complexes Of 4-(2-pyridylazo) Resorcinol - M. Awadallah, Ramadan (Asian Journal of Chemistry, 2010)
The reaction between copper(II), Zinc(II) and cadmium(II) and 4-(2-pyridylazo) resorcinol leads to the formation of complexes having the formula MnXmLy [M ═ Cu(II), Zn(II) or Cd(II); n ═ 1 or 2, X ═ Cl, m ═ 0,1; L ═ 4-(2-pycidylazo) resorcinol (PAR), y ═ 0.5, lor 2]. The complex formation was studied by conductometric titrations and conductometric measurements and spectrophotometrically at pH 2.15-11.25. The Cu(II)-Zn(II)- and Cd(II)-PAR complexes absorb at λ═ 500 (pH ═ 9.81), 495 (pH ═ 8.12) and 480 nm (pH ═ 8.75) respectively. Stoichiometry (2 : 1, 11 : 1, 1 : 2), formation stability constants and thermodynamic parameters (ΔºG, ΔH and ΔS) have been evaluated and the values of which are in the order Cd- > Zn- > Cu-PAR complexes. The reagent is made use of for the determination of 0.63 ppm Cu, 0.32 ppm Zn and 0.42 ppm Cd.